Current Knowledge and Future Challenges on Bacterial Degradation of the Highly Complex Petroleum Products Asphaltenes and Resins - Nzila, Alexis; Musa, Musa M. (Frontiers in Environmental Science, 2021)
Petroleum products consist mainly of aliphatics, aromatics, asphaltenes and resins. After oil exploitation, the concentrations of asphaltenes and resins are high in oil reservoirs; however, they are also the petroleum pollutants most recalcitrant to degradation, leading to high oil viscosity. A sizable amount of work has been dedicated to understand the degradation mechanisms of aliphatics and aromatics; however, in comparison, little work has been carried out on asphaltene and resin degradation. This review discusses our current knowledge on the understanding of asphaltene and resin degradation. More specifically, it sheds light on work carried out to date on the degradation of these pollutants, and highlights the major gaps that limit our understanding of their degradation pathways. It also presents new potential research areas that can be explored to fill in these gaps.